Orang Tua, Modal Agama, dan Pengetahuan Dalam Pengembangan Kecerdasan IESQ Anak - Fika (Jurnal Psikologi Islam, 2021)
This study aims to explain the forms and patterns of parental roles, as well as the relationship between parental roles and religious capital, as well as knowledge about children's IESQ development. The research method used is library research, with descriptive analytical techniques used in qualitative data analysis and psychological approaches. By investigating the forms and patterns of parental roles in parenting, as well as the relationship between parental roles and religious capital, and knowledge of children's IESQ development. The theoretical analysis uses Albert Bandura's Social Cognitive theory, which is known as an imitation-based learning model. The imitation in question is imitating what he sees around him, which can include teachers, parents, and playmates. Parents with strong religious capital or knowledge can demand obedience and become good role models for their children's mental, personal and behavioral development. If parents are accustomed to acting and having noble character, being obedient to God, carrying out religious laws, and having a social spirit, the traits that exist in their parents will appear and be formed in the child, because he will see and imitate what he sees in his daily life. based on the actions of their parents. Parental knowledge is also very important in developing children's IES intelligence, because parents can accompany and develop children's intelligence as much as possible. As the key to developing children's IES intelligence, the family environment, especially parents, plays an important role in directing and developing the potential of each child optimally.